2016
DOI: 10.1111/acem.13026
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Imaging Strategies for Occult Hip Fractures: A Decision and Cost–Effectiveness Analysis

Abstract: MRI is a cost-effective strategy for the diagnosis of an occult hip fracture. For facilities without MRI capability, the most cost-effective strategy depends on the cost of the interfacility transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 40 publications
(111 reference statements)
0
12
0
Order By: Relevance
“…For example, Yun et al demonstrated that the selective MRI strategy (performing CT and, if negative, performing MRI) in patients with occult hip fractures was dominated by the universal MRI strategy. 19 Incremental costeffectiveness ratios (ICERs) are only necessary and meaningful if a strategy is both more costly and more effective, or both less costly and less effective. By using the appropriate cost perspective and the additional health benefit in QALYs, the costs per QALY can be calculated and compared with a predefined threshold value.…”
Section: Cost-effectiveness Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Yun et al demonstrated that the selective MRI strategy (performing CT and, if negative, performing MRI) in patients with occult hip fractures was dominated by the universal MRI strategy. 19 Incremental costeffectiveness ratios (ICERs) are only necessary and meaningful if a strategy is both more costly and more effective, or both less costly and less effective. By using the appropriate cost perspective and the additional health benefit in QALYs, the costs per QALY can be calculated and compared with a predefined threshold value.…”
Section: Cost-effectiveness Analysismentioning
confidence: 99%
“…For example, in a recent study, Yun et al concluded that MRI provides an additional 0.05 QALY at an incremental cost of $1,227 with an ICER of $25,438/QALY in patients with occult hip fractures. 19…”
Section: Cost-effectiveness Analysismentioning
confidence: 99%
See 3 more Smart Citations